Utilization of Injection Pad Set Technology and Educational Videos in Optimizing Insulin Therapy in Type 2 Diabetes Mellitus Patients - Purwaningsih, Iswanti; Rayasari, Fitrian; Anggraeni, Dewi; Jumaiyah, Wati; Hernani, Eny (Global Health Science Group, 2024)
One of the pharmacologically controlled blood sugar levels in T2DM patients is by giving the correct insulin injection including the dose, method, time, and location, the success parameters of insulin injection include the injection location, injection procedure, and insulin management where everything will depend on glycemic control. Complications that appear at the injection site include bruising, pain, and swelling that indicate the occurrence of Lipohypertrophy (LH) Lipodystrophy is a form of lipohypertrophy (LH) which is a common complication that often occurs in T2DM patients with insulin injection therapy. This lipodystrophy will also be one of the factors that cause other T2DM complications. Method: the design in this study is One-Group Pre-test-Post-test Design, with a sampling of 14 DM patients who receive insulin injection therapy. The research period is from May to July 2024. Education using injection pad sets and educational videos on insulin injection techniques, observation of skills, and signs of lipodystrophy using questionnaires. Results: The results showed a decrease in the average blood sugar level before and after the educational intervention with a P-value of <0.001, the average patient's skill insulin injection showed an increase with a P-value of <0.001, the incidence of lipodystrophy showed that out of three areas of insulin injection, there was one location where lipodystrophy was found, namely in the arm area. With a p-value of 0.041. Conclusion: in this study, modifications are needed in the use of media or techniques in educating DM patients on insulin injection. Education can be repeated in both new and old patients on insulin. Patients need to be explained how to independently check for signs of lipodystrophy or changes in the injection site area